Individual factors affecting the employability of Information Systems graduates in Cape Town, South Africa: Employed graduates and employer perspectives - Kundaeli, Flora (Department of Information Systems, 2017)
Graduate employability has been a common subject among researchers, governments and higher education systems around the world. However, while there is a lot of information and numerous models that inform on graduate employability, there has been limited empirical research in this area. Furthermore, most employability studies have been conducted in the United Kingdom and other parts of the world, which may not be representative of the South African environment. Despite Information Technology (IT) being one of the most sought after qualification by employers in South Africa, it still remains unclear as to why many IT graduates struggle to secure jobs after graduation. This study provides insight into the concept of employability in South Africa, with a particular focus on Information Systems (IS) graduates in Cape Town. The study addresses three research questions: What individual factors affect the employability of IS graduates in Cape Town, South Africa? Who is responsible for graduate employability in South Africa? How can employability be embedded into South African curriculums? The study was guided by Dacre Pool and Sewell's (2007) CareerEDGE model, and Yorke and Knight's (2006) definition of employability. Data was collected from 19 individuals using focus group and in-depth interviews. Results showed that career development learning, experience (work and life), degree subject knowledge, skills and understanding, generic skills, emotional intelligence, self-confidence and reflection and evaluation affected one's employability. Employers, graduates and academic institutions were each expected to play a role in graduate employability. To embed employability into curriculums, universities need to ensure that curriculums are aligned to industry needs, that there is a balance between the soft and hard skills taught and that effective methods of teaching are being used. Universities are also encouraged to incorporate experiential learning in their programs and to provide proper career guidance counselling services to students early in their degree studies, so that students can make informed decisions regarding career paths and goals, and start tailoring their skills accordingly. The research contributes to the existing literature and debate on graduate employability, and builds upon the employability factors and relationships defined by Dacre Pool and Sewell's (2007) CareerEDGE model. The research also contributes to the existing theories on employability by providing empirical evidence regarding individual graduate employability factors. Lastly the research provides recommendations for practice and for improving employability in graduates.